2018
DOI: 10.1038/s41380-018-0243-x
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent exposure to Δ9-tetrahydrocannabinol alters the transcriptional trajectory and dendritic architecture of prefrontal pyramidal neurons

Abstract: Neuronal circuits within the prefrontal cortex (PFC) mediate higher cognitive functions and emotional regulation that are disrupted in psychiatric disorders. The PFC undergoes significant maturation during adolescence, a period when cannabis use in humans has been linked to subsequent vulnerability to psychiatric disorders such as addiction and schizophrenia. Here, we investigated in a rat model the effects of adolescent exposure to Δ9-tetrahydrocannabinol (THC), a psychoactive component of cannabis, on the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
72
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(85 citation statements)
references
References 64 publications
(65 reference statements)
8
72
3
2
Order By: Relevance
“…Cannabis has been shown to work on developing organisms by a number of complex pathways which have been summarized elsewhere ( Reece et al, 2016 ; Reece and Hulse, 2016 ; Reece, 2018 ; Reece and Hulse, 2019b, 2020b, 2020c ). Briefly stated cannabinoids have been shown to work via: interference with synapse formation by interruption of neurexin / neuroligin scaffolding ( Foldy et al, 2013 ; Anderson et al, 2015 ; Wang, 2016 ); impeding notch signaling ( Lu et al, 2006 ; Newton et al, 2009 ; Tanveer et al, 2012 ; Kim et al, 2014 ) an important morphogen for cardiac, vascular, brain, and hemopoietic tissues ( Carlson, 2014 ); impeding robo/slit signaling with effects on human neocortical exuberant outgrowth, nerve and blood vessel guidance, tissue development in kidney, breast, lung and muscle ( Alpar et al, 2014 ; Blockus and Chedotal, 2016 ), spinal cord midline guidance, several neurodevelopmental disorders including dyslexia ( Galaburda et al, 2006 ) and psychopathy ( Viding et al, 2010 ); impeding axonal guidance by interference with stathmin signaling ( Tortoriello et al, 2014 ); cytoskeletal impairment affecting the actin cytoskeleton ( Wang et al, 2011 ; Miller et al, 2019 ) and microtubule structure and function ( Wang et al, 2011 ; Miller et al, 2019 ); defects on egg and sperm development including gross sperm deformities involving head and tail malformations ( Morishima, 1984 ; Hembree et al, 1999 ; Szutorisz and Hurd, 2016 ; Johnson et al, 2017 ; Murphy et al, 2018 ); impairment of mitochondrial function ( Sarafian et al, 2003 ; Sarafian et al, 2006 ); impairment of sperm mitochondrial function ( Rossato et al, 2005 ); impairment of replacement of sperm histones by protamines ( Chioccarelli et al, 2010 ); epigenetic effects ( Yang et al, 2014 ) and micronucleus effects ( Van Went, 1978 ; Piatti et al, 1989 ; Parolini and Binelli, 2014 ; Reece and Hulse, 2016 ) including cytoplasmic bridges and nuclear blebbing ( Morishima, 1984 ; Huang et al, 1999 ; Russo et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cannabis has been shown to work on developing organisms by a number of complex pathways which have been summarized elsewhere ( Reece et al, 2016 ; Reece and Hulse, 2016 ; Reece, 2018 ; Reece and Hulse, 2019b, 2020b, 2020c ). Briefly stated cannabinoids have been shown to work via: interference with synapse formation by interruption of neurexin / neuroligin scaffolding ( Foldy et al, 2013 ; Anderson et al, 2015 ; Wang, 2016 ); impeding notch signaling ( Lu et al, 2006 ; Newton et al, 2009 ; Tanveer et al, 2012 ; Kim et al, 2014 ) an important morphogen for cardiac, vascular, brain, and hemopoietic tissues ( Carlson, 2014 ); impeding robo/slit signaling with effects on human neocortical exuberant outgrowth, nerve and blood vessel guidance, tissue development in kidney, breast, lung and muscle ( Alpar et al, 2014 ; Blockus and Chedotal, 2016 ), spinal cord midline guidance, several neurodevelopmental disorders including dyslexia ( Galaburda et al, 2006 ) and psychopathy ( Viding et al, 2010 ); impeding axonal guidance by interference with stathmin signaling ( Tortoriello et al, 2014 ); cytoskeletal impairment affecting the actin cytoskeleton ( Wang et al, 2011 ; Miller et al, 2019 ) and microtubule structure and function ( Wang et al, 2011 ; Miller et al, 2019 ); defects on egg and sperm development including gross sperm deformities involving head and tail malformations ( Morishima, 1984 ; Hembree et al, 1999 ; Szutorisz and Hurd, 2016 ; Johnson et al, 2017 ; Murphy et al, 2018 ); impairment of mitochondrial function ( Sarafian et al, 2003 ; Sarafian et al, 2006 ); impairment of sperm mitochondrial function ( Rossato et al, 2005 ); impairment of replacement of sperm histones by protamines ( Chioccarelli et al, 2010 ); epigenetic effects ( Yang et al, 2014 ) and micronucleus effects ( Van Went, 1978 ; Piatti et al, 1989 ; Parolini and Binelli, 2014 ; Reece and Hulse, 2016 ) including cytoplasmic bridges and nuclear blebbing ( Morishima, 1984 ; Huang et al, 1999 ; Russo et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…One impressive longitudinal New Zealand study of 1,037 children followed from birth to age 38 years found progressive, serious and dose-related declines in IQ and a global decline in all measures of executive cortical functioning, which accrued with continued use and were obvious to external observers [45]. Cannabis has been shown to impair synapse formation [19,22] and induce dendritic pruning [21] which has been causally linked with the mechanisms of forgetting [50,51] and to adversely affect the slit/robo ratio [18,52,53] a key messenger-ligand pair controlling the extent of exuberant mammalian neocortical development [54,55]. All of these widespread neurocognitive cannabis-induced defects are consistent with its multifarous known mechanisms of action and its intimate involvement in virtually every step of brain and neural network formation.…”
Section: Discussionmentioning
confidence: 99%
“…Ces anomalies s'accompagnent d'une diminution des protéines impliquées dans la plasticité synaptique et de l'expression de CB1R, ainsi que d'une perturbation de la maturation des systèmes dopaminergiques, glutamatergiques, sérotoninergique et GABAergique dans l'hippocampe et le cortex préfrontal [15,28] et même de la morphologie dendritique au niveau préfrontal [28]. Le THC à l'adolescence altère aussi l'expression de réseaux de gènes impliqués dans la morphogenèse cellulaire, le développement dendritique et l'organisation du cytosquelette au niveau préfrontal [29].…”
Section: Cannabis Et Adolescenceunclassified